18F-FDG PET in Liver Transplantation Setting of Hepatocellular Carcinoma: Predicting Histology?. (March 2016) - Bailly, Matthieu; Venel, Yann; Orain, Isabelle; Salamé, Ephrem; Ribeiro, Maria-Joao
Abstract : Purpose: The aim of this study was to evaluate the prognostic value of 18 F-FDG PET/CT by predicting histopathological findings in the pretransplant evaluation of patients with hepatocellular carcinoma (HCC). Patients and Methods: 18 F-FDG PET/CT findings of 34 patients with HCC who underwent liver transplantation were reviewed retrospectively. Visual and quantitative analysis (tumor standardized uptake values normalized to the background activity of the liver: SUVmax T/L) was done. PET tumor characteristics were compared with the histological analysis (differentiation and microvascular invasion). All patients were followed up (mean, 12 months). Results: Ten patients showed tumoral uptake greater than background activity (PET+). Higher-grade tumor was more common in the 18 F-FDG–avid tumor group ( P < 0.05). PET+ also showed more microvascular invasion at explant pathology ( P < 0.05). Only 1 patient PET+ developed HCC early recurrence (4 months) with an SUVmax T/L of 1.64. Conclusions: 18 F-FDG uptake is predictive for microvascular invasion and tumor differentiation. This examination has a prognostic value regarding tumor recurrence after liver transplantation for HCC.